Decompression Illness in Repetitive Breath-Hold Diving: Why Ischemic Lesions Involve the Brain? - Kohshi, Kiyotaka; Denoble, Petar J.; Tamaki, Hideki; Morimatsu, Yoshitaka; Ishitake, Tatsuya; Lemaître, Frédéric (Frontiers in Physiology, 2021)
Nitrogen (N2) accumulation in the blood and tissues can occur due to breath-hold (BH) diving. Post-dive venous gas emboli have been documented in commercial BH divers (Ama) after repetitive dives with short surface intervals. Hence, BH diving can theoretically cause decompression illness (DCI). “Taravana,” the diving syndrome described in Polynesian pearl divers by Cross in the 1960s, is likely DCI. It manifests mainly with cerebral involvements, especially stroke-like brain attacks with the spinal cord spared. Neuroradiological studies on Ama divers showed symptomatic and asymptomatic ischemic lesions in the cerebral cortex, subcortex, basal ganglia, brainstem, and cerebellum. These lesions localized in the external watershed areas and deep perforating arteries are compatible with cerebral arterial gas embolism. The underlying mechanisms remain to be elucidated. We consider that the most plausible mechanisms are arterialized venous gas bubbles passing through the lungs, occlude cerebral arteries and then expand from N2 influx from the occluded arteries and the brain The first aid normobaric oxygen appears beneficial. DCI prevention strategy includes avoiding long-lasting repetitive dives for more than several hours, prolonging the surface intervals. This article provides an overview of clinical manifestations of DCI following repetitive BH dives and discusses possible mechanisms based on clinical and neuroimaging studies.